Diffusive mass transport in agglomerated glassy fallout from a near-surface nuclear test. (15th February 2018) - Weisz, David G.; Jacobsen, Benjamin; Marks, Naomi E.; Knight, Kim B.; Isselhardt, Brett H.; Matzel, Jennifer E.
Abstract: Aerodynamically-shaped glassy fallout is formed when vapor phase constituents from the nuclear device are incorporated into molten carriers ( i.e. fallout precursor materials derived from soil or other near-field environmental debris). The effects of speciation and diffusive transport of condensing constituents are not well defined in models of fallout formation. Previously we reported observations of diffuse micrometer scale layers enriched in Na, Fe, Ca, and 235 U, and depleted in Al and Ti, at the interfaces of agglomerated fallout objects. Here, we derive the timescales of uranium mass transport in such fallout as it cools from 2500 K to 1500 K by applying a 1-dimensional planar diffusion model to the observed 235 U/ 30 Si variation at the interfaces. By modeling the thermal transport between the fireball and the carrier materials, the time of mass transport is calculated to be <0.6 s, <1 s, <2 s, and <3.5 s for fireball yields of 0.1 kt, 1 kt, 10 kt, and 100 kt respectively. Based on the calculated times of mass transport, a maximum temperature of deposition of uranium onto the carrier material of ∼2200 K is inferred (1σ uncertainty of ∼200 K). We also determine that the occurrence of micrometer scale layers of material enriched in relatively volatile Na-species as well as more refractory Ca-species provides evidence for an oxygen-rich fireball based on the vapor pressure of the two species under oxidizing conditions. These results represent the first application of diffusion-based modeling to derive material transport, thermal environments, and oxidation-speciation in near-surface nuclear detonation environments.